Human biomarkers of rapid antidepressant effects - Zarate, Carlos A. (2013)
Mood disorders such as major depressive disorder (MDD) and bipolar disorder (BD)—and their consequent effects on the individual and society—are among the most disabling and costly of all medical illnesses. While a number of antidepressant treatments are available in clinical practice, many patients still undergo multiple and lengthy medication trials before experiencing relief of symptoms. A tremendous need therefore exists to improve current treatment options, and to facilitate more rapid, successful treatment in patients suffering from the deleterious neurobiological effects of ongoing depression. Towards that end, ongoing research is exploring the identification of biomarkers that may be involved in prevention, diagnosis, treatment response, severity, or prognosis of depression. Biomarkers evaluating treatment response will be the focus of this review, given the importance of providing relief to patients in a more expedient and systematic manner. A novel approach to developing such biomarkers of response would incorporate interventions with a rapid onset of action—such as sleep deprivation or intravenous drugs (e.g. ketamine or scopolamine). This alternative translational model for new treatments in psychiatry would facilitate shorter studies, improve feasibility, and increase higher compound throughput testing for these devastating disorders.